Structure-controlled graphene electrocatalysts for high-performance H2O2 production. Issue 7 (25th May 2022) - Lee, Kyungbin; Lim, Jeonghoon; Lee, Michael J.; Ryu, Kun; Lee, Hoyoung; Kim, Jin Young; Ju, Hyunchul; Cho, Hyun-Seok; Kim, Byung-Hyun; Hatzell, Marta C.; Kang, Joonhee; Lee, Seung Woo
Abstract : A structure-mechanism-performance relationship of metal-free carbon catalysts for outstanding H2 O2 production activity and selectivity in alkaline media. Abstract : Metal-free carbon materials have emerged as cost-effective and high-performance catalysts for the production of hydrogen peroxide (H2 O2 ) through the two-electron oxygen reduction reaction (ORR). Here, we show that 3D crumpled graphene with controlled oxygen and defect configurations significantly improves the electrocatalytic production of H2 O2 . The crumpled graphene electrocatalyst with optimal defect structures and oxygen functional groups exhibits outstanding H2 O2 selectivity of 92–100% in a wide potential window of 0.05–0.7 V vs. reversible hydrogen electrode (RHE) and a high mass activity of 158 A g −1 at 0.65 V vs. RHE in alkaline media. In addition, the crumpled graphene catalyst showed an excellent H2 O2 production rate of 473.9 mmol gcat −1 h −1 and stability over 46 h at 0.4 V vs. RHE. Moreover, density functional theory calculations revealed the role of the functional groups and defect sites in the two-electron ORR pathway through the scaling relation between OOH and O adsorption strengths. These results establish a structure-mechanism-performance relationship of functionalized carbon catalysts for the effective production of H2 O2 .